Prevalence and Predictors of Food Insecurity in Urban Poor Fishery Households in Vietnam: A Cross-sectional Study - Nguyen Hoang My Thuyen (2022)
Food insecurity is a significant public health problem in Vietnam, and accompanied by poverty results in poor health and nutrition, particularly in vulnerable populations. Urban poor fishery households in coastal cities of Vietnam are striving for a living and are vulnerable to food insecurity. Guided by Bronfenbrenner’s Bioecological Theory, this cross-sectional study aimed to determine the prevalence of household food insecurity and identify multi-system factors predicting food insecurity in Vietnam’s urban poor fishery households. Through stratified random sampling, 420 eligible households from the two largest cities of a province in South Central Coastal Vietnam were recruited then responded to the structure questionnaires including the Food Insecurity Experience Scale, the Perceived Natural Disaster Influence instrument, the Chronic Health Condition form, the Social Network tool, the modified Social Support Questionnaire, the Short Food Literacy Questionnaire, and a scale of Transportation Quality, Access and Availability Assessment. Results revealed that 36.2% of the households had food insecurity. A multivariate logistic regression analysis found that overall food literacy, homeownership, number of social networks, and family support together significantly predicted household food insecurity. Before developing a program promoting household food security, the role of food literacy needed to be examined in an age-specific population. The findings suggest approaches to enhance household food security through strengthening social welfare, social networks and family support.